Causes and prevention of disorder of calcium-phosphorus exchange in rabbits - Eshburiyev Sobir; Mamatova Zamira; Achilov Odil; Karshiyev Usman; Aliyarov Soatmo’min; Eshimov D; Kholbekova Gulbeka; Sattorov Jamshid (BIO Web of Conferences, 2024)
Disorders of calcium and phosphorus metabolism in rabbits are caused by a violation of the ratio of calcium and phosphorus in their ration, and it was found that the supply rate of rabbits with nutritious substances in the diet is 85.46% calcium, 63.25% phosphorus, 64.0% carotene, 86.15% raw kletchatka, 91.17% dry matter, 91.2% digestible protein. Calcium-phosphorus metabolism disorders in rabbits are accompanied by sympto ms such as altered appetite (coprophagia), pale mucous membranes, hoarseness of the skin coating, loss of glare, the appearance of bulges in the ribs, as well as hypogemoglobinemia, hypocalcemia, hypophosphoremia. As a result of this pathology, abortions can be observed in mother rabbits, or their children born from them will be hypotrophic. Methods have been developed to prevent calcium and phosphorus exchange disorders in rabbits by giving granular lobster baits enriched with Nova Marks (vitamin-mineral premix) premix, mixing the Innoprovet probiotic in water. Granule feed (enriched with 1 kg of Nova Marx premix per 1tonna feed) + innoprovet 1 ml with 1 liter of water (for 7 days) in the period from the 10th day of calving to the 10th day after childbirth is more effective, ensuring an increase in hemoglobin in the blood by an average of 12.7 g/l, total protein in the blood serum-14.06 g/l, total calcium - 1.04 mmol/L and inorganic phosphorus. Vitamin-mineral premix, given in combination with probiotics, improves food digestion in the body of rabbits. This method of prophylaxis prevents calcium- phosphorus exchange disorders in rabbits, in which the increase in body weight is on average 0.51 kg higher than the control.